Pyogenic Liver Abscess Caused by Staphylococcus hominis: A Case Report - Ze-Hua Zhao; Yu-Chen Fan; Kai Wang; Stijn van der Veen (Infectious Microbes & Diseases, 2022)
Abstract. Staphylococcus hominis is a component of the normal human microflora and is considered to be an opportunistic pathogen that may cause a variety of infections. It has been reported to cause bacteremia, endocarditis and endophthalmitis. However, abscesses caused by S. hominis are rarely documented. Here, we describe a case of pyogenic liver abscesses caused by S. hominis. Laboratory tests, imaging examinations, and abscess puncture fluid culture were used to identify the etiology and pathogenic bacterium. This case suggests that percutaneous drainage and targeted antibiotic treatment according to the results of antimicrobial susceptibility tests are effective therapeutic approaches for pyogenic liver abscesses caused by S. hominis.